N-Substituted pyrazole-3-carboxamides as inhibitors of human 15-lipoxygenase. Issue 15 (1st August 2015) - Pelcman, Benjamin; Sanin, Andrei; Nilsson, Peter; Schaal, Wesley; Olofsson, Kristofer; Krog-Jensen, Christian; Forsell, Pontus; Hallberg, Anders; Larhed, Mats; Boesen, Thomas; Kromann, Hasse; Claesson, Hans-Erik
Graphical abstract: Abstract: High-throughput screening was used to find selective inhibitors of human 15-lipoxygenase-1 (15-LOX-1). One hit, a 1-benzoyl substituted pyrazole-3-carboxanilide (1a ), was used as a starting point in a program to develop potent and selective 15-LOX-1 inhibitors.